Metagenomics: A Modern-day Tool for Exploring the Diverse Microbial Communities of East Kolkata Wetland - Chakraborty, Medha; Das, Samprit; Chaurasia, Sania; Saha, Mousumi; Sarkar, Agniswar (Microbiology and Biotechnology Research: An Overview Vol. 1, 2025)
Metagenomics is a powerful sequencing approach that enables culture-independent analysis of complex microbial communities, transforming microbial ecology. The East Kolkata Wetland (EKW), a vital ecosystem, harbors diverse microbes essential for wastewater treatment, nutrient cycling, and bioremediation. Traditional methods often fail to capture this diversity. This chapter highlights the role of metagenomic sequencing in profiling EKW’s microbial communities, revealing key consortia involved in organic matter degradation, nitrogen cycling, and pollutant remediation. These insights support sustainable wetland management and its function as a natural biofilter. Integrating metagenomics with bioinformatics enhances ecological monitoring, conservation, and environmental applications.